Visualization and characterization of interfacial polymerization layer formation. Issue 2 (25th November 2014) - Zhang, Yali; Benes, Nieck E.; Lammertink, Rob G. H.
Abstract : A microfluidic device is designed and used to investigate interfacial polymerization film formation in situ . Abstract : We present a microfluidic platform to visualize the formation of free-standing films by interfacial polymerization. A microfluidic device is fabricated, with an array of micropillars to stabilize an aqueous–organic interface that allows a direct observation of the films formation process via optical microscopy. Three different amines are selected to react with trimesoyl chloride: piperazine, JEFFAMINE ® D-230, and an ammonium functionalized polyhedral oligomeric silsesquioxane. Tracking the formation of the free-standing films in time reveals strong effects of the characteristics of the amine precursor on the morphological evolution of the films. Piperazine exhibits a rapid reaction with trimesoyl chloride, forming a film up to 20 μm thick within half a minute. JEFFAMINE ® D-230 displays much slower film formation kinetics. The location of the polymerization reaction was initially in the aqueous phase and then shifted into the organic phase. Our in situ real-time observations provide information on the kinetics and the changing location of the polymerization. This provides insights with important implications for fine-tuning of interfacial polymerizations for various applications.